The going astray of Hegelian dialectics between Logic and Nature (Revista Eletrônica Estudos Hegelianos, 2024)
The aim of this study is to investigate the relationship between Logic and Nature within the Hegelian system. Our focus lies on the status of the categories of nature: are they merely a redoubling of the equivalent logical categories or is there a substantial difference between them? First, we analyze the secondary literature on the subject and conclude that it falls short of the complexity of the problem. Secondly, we make a detailed comparison between the Philosophy of Nature and the Science of Logic and hypothesize that the natural categories presuppose logic as a standard, that is, a kind of ruler that determines what the ideal development would be; however, as nature fails to faithfully reproduce this standard, its categories deviate considerably from the logical categories.